Education development in Gender at the University: Field of specific subjects or cross education? (2015)
In this article, there is a discussion in the outcomes between to receive education development through specific or transversely subjects. The persistence of gender stereotypes and the sexual division of in the job is related to the lack of social awareness, due, among other factors to the lack of education in gender issues. This instruction is necessary to reflect and ´deconstruct´ messages about gender to reveal the ideological premises and hierarchies and the hierarchies in the underlying messages. The main objective is to note the importance of receiving training in gender at the University. It proposes to compare the results of the surveys aimed to the students in the bachelor of Science of Work and in Business Administration and Management, and see if there are differences between the two groups, both in relation to their training on the subject, such as with their behavior and attitudes compared to certain genderrelated issues. In addition, one could try to see, if there is a difference, to what extent can be derived from the education received. Past surveys have been to a representative sample of students of both degrees and have been applied the appropriate statistical techniques through the software SPSS. Work results reinforce the initial idea of the need to include subjects that provide gender educational programs and university degrees and raise not only disciplinary knowledge focused ‘knowing’ and guided professionals ‘know-how’, but also attitudes for an ethical commitment aimed at gender equity.